0
$\begingroup$

$$\lnot \forall y: Y.A\vdash \exists y: Y.(A\rightarrow B)$$

Need to prove that LHS entails RHS, however I'm confused as to how to do it. Never used a negation on a universal quantifier before.

Any help would be appreciated.

$\endgroup$
2
$\begingroup$

HINT $$\lnot \forall y: Y.A \equiv \exists y: \lnot Y.A$$

$\endgroup$
  • $\begingroup$ Thanks, I researched on De Morgan's for Quantifiers and figured it out! $\endgroup$ – user114083 Dec 7 '13 at 11:26

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.